Uso de álcool e tabaco entre estudantes da saúde de uma universidade pública - Souza, Renata Santos de (2008)
In recent years a number of studies have been devoted to the use of psychoactive drugs among college students, a particularly vulnerable population group. This study aims at investigating tobacco and alcohol use in particular among the students of Centro de Ciências da Saúde(CCS), which comprise Medical, Nursing, Dental and Pharmacy Schools, at Universidade Federal do Espírito Santo. An exploratory, descriptive, transversal and quantitative design was chosen and 668 students were surveyed through a modified version of the questionnaire developed by WHO’s Research and Reporting Project on the Epidemiology of Drug Dependence”. A descriptive statistical analysis was carried out with the help of the Statistical Package for the Social Science software (SPSS v. 15) followed by a chi-square test, at a 5% level of significance level. The data gathered show a prevalence of female college students (67,4%), the 20-22 age group (51,2%), and A (30,7%) and B (44,0%) social classes; 86,4% of the students reported lifetime use of alcohol, 78% yearly, 59% monthly and 15,4% frequent use while 6,0% reported heavy use of the substance. As for tobacco, 24,9% of the respondents reported lifetime use, 13,2% yearly, 3,0 % monthly, 1,6% frequent use while 1,2% reported heavy use. Alcohol use is correlated with students’ gender, undergraduate course, and relationship with their fathers, the consumption being the highest among male dental and medical students and the lowest among students with excellent or good relationship with their fathers. Tobacco use is associated with gender, social class, undergraduate course, and personality traits of their parents, the consumption being the highest among male dental students in the A-B social class spectrum. The lowest tobacco use rates were among college students who evaluated their parents as being moderate and the highest among those who evaluate their parents as being liberal. The results point to the need to establish both a permanent awareness and prevention programme, with the inclusion of alcohol and tobacco issues in the students’ curricula, and a treatment plan for addicted students.